THE CONCEPT OF STUDENT AND TEACHER ETHICS IN THE BOOK OF TAISIRUL KHALAQ BY HAFIDZ HASAN MAS'UDI - maila sakinah; Ahmad Zuhdi; Muhammad Saefullah (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
This study aims to examine the concept of student and teacher ethics in the book Taisirul Khalaq by Hafidz Hasan Mas'udi and its relevance to education in the modern era. This study uses a qualitative approach with library research. The main data source is the book Taisirul Khalaq, while secondary data are obtained from various relevant literature. Data collection techniques are carried out through documentation studies and online data searches, with analysis using content analysis and discourse analysis methods. The results show that student ethics include ethics towards oneself, teachers, and fellow friends, such as avoiding arrogance, being honest, humble, maintaining the trust of knowledge, and respecting teachers and honoring friends. Meanwhile, teacher ethics include the qualities of piety, humility, gentleness, and ethics in teaching, such as being wise, compassionate, giving advice, and not burdening students beyond their capabilities. These ethical concepts have strong relevance to education in the modern era, especially in responding to the moral crisis, declining respect for teachers, and the challenges of technological development. Therefore, the ethical values ​​in this book are important to be internalized in education in order to form a generation that is knowledgeable and has noble morals